Creative techniques of teaching group dynamics skills in social studies (intermediate fast learners) - Garcia, Lerma T. (1973)
The study discussed some techniques that are aimed at preparing fast learners in their role in a democratic society. The techniques discussed in this paper are selected on the rationale that they best develop group dynamics skills for the fast learning group. These methods are brain-storming, class discussion, buzz session, panel discussion, role playing and sociodrama. Principles in creative teaching of social studies are briefly discussed as an overview of the various techniques in teaching group dynamics. The needed information for this study were gathered through library research and materials from the Bureau of Public Schools.